1995
DOI: 10.1074/jbc.270.22.13567
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Transforming Growth Factor Type III Receptor in Vascular Endothelial Cells Increases Their Responsiveness to Transforming Growth Factor β2

Abstract: Bovine aortic endothelial cells (BAECs) express both type I and type II receptors for transforming growth factor beta (TGF beta). These cells respond to TGF beta 1 but are relatively refractory to another isoform of TGF beta, termed TGF beta 2. TGF beta s are thought to signal through receptor complexes composed of type I and/or type II receptors, both of which appear to be functional serine-threonine kinases. The TGF beta type III receptor, on the other hand, does not seem to have any direct signaling capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 42 publications
3
78
0
Order By: Relevance
“…In transgenic mice with a targeted deletion of the TGF-b1 gene signaling through TGF-b2 and TGF-b3 is still present and similarly, overexpression of TGF-b1 could also alter the expression of TGF-b2 and TGF-b3. Because all three isoforms of TGF-b utilize the type II receptor for signal transduction (Cheifetz et al, 1990;Sankar et al, 1995), expression of a dominant negative receptor mutant suppresses signaling of all TGF-b isoforms. Thus, a phenotype evoked by disturbance of the Suppression of TGF-b signaling C Amendt et al balance of the three isoforms is avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In transgenic mice with a targeted deletion of the TGF-b1 gene signaling through TGF-b2 and TGF-b3 is still present and similarly, overexpression of TGF-b1 could also alter the expression of TGF-b2 and TGF-b3. Because all three isoforms of TGF-b utilize the type II receptor for signal transduction (Cheifetz et al, 1990;Sankar et al, 1995), expression of a dominant negative receptor mutant suppresses signaling of all TGF-b isoforms. Thus, a phenotype evoked by disturbance of the Suppression of TGF-b signaling C Amendt et al balance of the three isoforms is avoided.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has several advantages. It is possible to interfere with signal transduction of all three isotypes of TGF-b, TGF-b1, -b2, -b3 (Cheifetz et al, 1990;Sankar et al, 1995). Furthermore, the tissue speci®c expression cassette targets transgene expression to speci®c tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Because tyrosine phosphorylation of FAK and paxillin phosphorylation are associated with assembly of adhesion foci (14), their phosphorylations may help stabilize the advancing lamellipodia (10,11). Such a role for FAK and paxillin in lamellipodial advance could explain why FAK expression correlates with cell motility (41)(42)(43). Lamellipodial extension is also critical for growth cone migration (16), but at this time, the function of paxillin and FAK in this regard remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts secreted TGF-β dose-dependently when TβRI and TβRII [74]. In primary fetal rat osteoblasts it has been shown that high levels of PGE 2 may increase TβRIII expression and in this way delay TGF-β-dependent activation of osteoblasts during the initial stabilization phase before cell replication and bone repair [75].…”
Section: Effects Of Dietary Polyunsaturated Fatty Acids and Their Promentioning
confidence: 99%